APPLICATION OF QUALITY FUNCTION DEPLOYMENT TO IMPROVE THE QUALITY OF DRY FISH BLEBERAN IN BENGKULU CITY - Evanila Silvia (BPFP Faperta UNIB, 2013)
The research objective is to determine the customer expectations, the activities process and their’s importance level; determine the relationship between customer expectations and process activity; determine the product’s performance against competitor’s product; and formulate recommendations for improving the product quality. The method used is Quality Function Deployment (QFD) with 42 persons as consumer respondents. The results showed that the importance level of the consumer expectations to Bleberan dried fish by ranking are moisture content, shelf life, shape, texture, price, aroma, microorganism content, colors, packaging and additives. The importance level of process activity is the drying process, packing, salting, separation and sorting, and washing or cleaning. The eminence of Bleberan dried fish in Bengkulu City is for its water content, texture and aroma when it compared to competitor products. Unfortunately, the shelf life, price and packaging are still below competitors' products. While Shape, content of microorganisms and additives of Bleberan dried fish in Bengkulu city is equal to competitors' products. The quality attributes that need to be improved is the shelf life, packaging and content of microorganisms. According to quality improvement, the three main activities of process that must be improved are drying process, packing and salting.